Earthworm Cultivation by Utilizing Organic and Inorganic Waste - Amirah Mustarin; Nurmila Nurmila; Muhammad Wiharto; Kasmawati Kasmawati; Asrijal Asrijal (PT. Global Research Collaboration, 2024)
The new paradigm of waste today is that it can be a resource. The concept of waste management is carried out with the 3R concept (reduce, reuse, and recycle). Reuse activities on billboard advertising waste are one form of waste use that can be reused for organic fertilizer production purposes. Efforts to manage solid advertising waste are carried out by the Sikamaseang Group, Maros Baru District, Maros Regency, by utilizing the waste as a container in the production of vermicast (worm waste), which can be used in fish farming activities in ponds. Training and coaching activities for members of the Sikamaseang Group farmer group are carried out actively with demonstration and practice methods involving all program participants. The results of these activities are containers and media for cultivating Lumbricus rubellus worms, which are used as organic fertilizer in fish farming. The knowledge and skills possessed by the participants can be applied to the production of fertilizer needs in fisheries activities in Maros Baru District, Maros Regency.